Une illusion de joie dans beaucoup de souffrances : en finir avec la « fête épique » - Philippe Haugeard (Revue des Langues Romanes)
This paper is intended to challenge the well-established idea that the “chanson de geste” would celebrate the war in the form of a joyous melee in which the pleasure of killing would be accompanied by search for glory: the critic was thus able to speak of “epic feast” to qualify episodes of battle. The texts which serve to found this reading nevertheless give another image of the war: if it can provide moments of joy, it is punctually, and this joy is never that of killing or slaughtering. On the contrary, war is an experience of pain, and the dominant emotion is not joy but anger. It appears that criticism has confused “joy” and “energy”: it is the latter that is celebrated, and aesthetically enhanced by the epic writing. This observation leads to a re-examination of the nature of epic reception: heroic exaltation is articulated in compassion and lamentation.